If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 4 + -3c = -9 + c + 15 Reorder the terms: 4 + 2c + -3c = -9 + c + 15 Combine like terms: 2c + -3c = -1c 4 + -1c = -9 + c + 15 Reorder the terms: 4 + -1c = -9 + 15 + c Combine like terms: -9 + 15 = 6 4 + -1c = 6 + c Solving 4 + -1c = 6 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 4 + -1c + -1c = 6 + c + -1c Combine like terms: -1c + -1c = -2c 4 + -2c = 6 + c + -1c Combine like terms: c + -1c = 0 4 + -2c = 6 + 0 4 + -2c = 6 Add '-4' to each side of the equation. 4 + -4 + -2c = 6 + -4 Combine like terms: 4 + -4 = 0 0 + -2c = 6 + -4 -2c = 6 + -4 Combine like terms: 6 + -4 = 2 -2c = 2 Divide each side by '-2'. c = -1 Simplifying c = -1
| 7C+1=50 | | x-4.5=3 | | 10.6p+15=205.8 | | 10=50x | | 8s-12=52 | | -x-3x+20=x | | 3xyz-y+4x-y= | | 45p=168 | | 2f-81=11 | | 27=x+14 | | -36-9x=-12x+3 | | (5x-2)(7x+8)= | | 2(1/2x+1)=-3(2x-1)+4(2x+1) | | -8x+-3x= | | 2x=3x-22 | | 3r-7=17r | | 400p+20=680 | | 2x+x+2x=126 | | 32.8=8n | | 9s=-20 | | (-3+2i)-(4-4i)= | | 7-2p=12p | | (8x^2-3x^3)-(2x^2-5x^3)= | | 4x+14=-3x | | 7(4+h)h=9 | | -3x+2x+9y-2x= | | 5n+3=2(n+2)-3m | | -8x-3x= | | 7x+7-9(x+1)=5x+2 | | 9v^2+59v-28=0 | | 5xy-3xy+x^2= | | -3b+7=-5 |